Effect of a vitamin-mineral complex on pregnancy after fixed time artificial insemination - Leonetti Unzué, Tomas (2020)
The aim of this study was to evaluate the effect of a parenteral treatment with vitamins and minerals on the percentage of pregnancy in heifers after a fixed-time artificial insemination (FTAI) scheme as well as to determine possible relationships between the response to the treatment and the Reproductive Tract Score (RTS). A total of 360 heifers from three farms were used (A, B and C). On day 0, the animals were divided into two groups according to their RTS. A group was supplemented via i.m. with a commercial vitamin-mineral complex (V+M Group) and the other one remained as a control group. Simultaneously, an intravaginal device with 0.5 g of progesterone was placed and 2 mg of estradiol benzoate was injected. On day 7, the device was removed and 500 µg of D(+) cloprostenol and 1 mg of estradiol cypionate were injected. The FTAI was performed between 48 and 56 h after the device was removed, using frozen semen in A and C, and two bulls in B. Pregnancy diagnosis was performed by ultrasonography at 32 days of the FTAI. The pregnancy rate was 56.9% in A and 52.0% in C, without significant difference between treatments, but it was 76.6% for V+M and 57.8% for the control in farm B (p=0.03). There was no effect of RTS and RTS-Treatment interaction. In conclusion, vitamin/mineral supplementation applied parenterally at the beginning of an FTAI protocol in 15-month heifers has variable results.